2014
DOI: 10.1186/bf03352193
|View full text |Cite
|
Sign up to set email alerts
|

Broadband converted phases from midmantle discontinuities

Abstract: A technique for detecting intermediate-period (6-12 s) Sd P phases converted from S to P at a depth d in the source region is described. Previously, these phases were detected in short-period array recordings of deep events. The main idea of our technique is to deconvolve the vertical component of a single record by the S waveform, and to stack the deconvolved components of a number of records, with appropriate time-shift corrections accounting for the difference of epicentral distance. Using this technique, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 17 publications
2
23
0
Order By: Relevance
“…These reflectors may be related to the bottom of the subducted slab, or represent phase transitions in slab specific compositions. Deuss and Woodhouse (2002) found reflectors at 1,200 km depth in stacks for the Indonesian subduction zone region, at the same depth and location where receiver function studies have also found lower mantle reflectors (Vinnik et al 1998(Vinnik et al , 2001.…”
Section: Lower Mantle Reflectorsmentioning
confidence: 86%
“…These reflectors may be related to the bottom of the subducted slab, or represent phase transitions in slab specific compositions. Deuss and Woodhouse (2002) found reflectors at 1,200 km depth in stacks for the Indonesian subduction zone region, at the same depth and location where receiver function studies have also found lower mantle reflectors (Vinnik et al 1998(Vinnik et al , 2001.…”
Section: Lower Mantle Reflectorsmentioning
confidence: 86%
“…There are also widespread reports of seismic discontinuities between 800 and 1200 km depth (e.g. Kawakatsu & Niu 1994, 1996; Vinnik et al 1998), which could separate regions of somewhat different chemical composition. Interestingly, 1000 km also corresponds to the approximate depth of an order of magnitude increase in mantle viscosity inferred by Mitrovica & Forte (1997, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…2000; Fukao et al . 2000) and with the depth of the mid‐mantle discontinuity (Kawakatsu & Niu 1994; Niu & Kawakatsu 1997; Vinnik et al . 1998).…”
Section: Discussionmentioning
confidence: 99%